I'm fine, but you appear to be sinking - Krow, Leyna (Featherproof Books, 2017)
In I'm Fine, But You Appear to Be Sinking the strange and the mundane collide. These are stories of strange experiences set in familiar places, and of familiar experiences set in strange places. Many of the pieces in I'm Fine take place close to home, in suburban neighborhoods, or rural communities. The settings are conventional, yet something unexpected, or even magical, is occurring. In one piece, a couple speculates about random objects that appear without reason in their backyard. In another, neighbors try to figure out if a local meth dealer is keeping a live tiger captive on his property. In other pieces, it's the setting that's fantastical, but the characters' reactions that remain ordinary, like in the titular story where a journalist lost at sea and hunted by a mythical ocean creature admits to struggling with loneliness and isolation in much the same way he does even when he's safe at home.